Weather monitoring for local area based on Lora module using STM32 Microcontroller - Saputra, Rifaldo; Yuhendri, Muldi; Mukhaiyar, Riki; Ranuharja, Fadhli (Journal of Industrial Automation and Electrical Engineering, 2025)
The need for an efficient and reliable weather monitoring system in areas with limited communication infrastructure has led to the development of an Internet of Things (IoT)-based solution utilizing LoRa (Long Range) technology. This study presents the design and implementation of a local-area weather monitoring system using the STM32F103C8T6 microcontroller and the LoRa RA-02 communication module. The system monitors environmental parameters such as temperature, humidity, wind speed, and air pressure using various sensors including DHT-21, BMP280, A3114, and INA219. Sensor data is collected by the transmitter node and sent via LoRa to a receiver node equipped with an ESP32 microcontroller. The receiver processes the data and sends it to the Blynk IoT platform and Google Sheets for visualization and storage. Experimental results show reliable transmission over distances up to 530 meters in dense environments and 2 kilometers in open areas. The system demonstrated low power consumption, making it suitable for solar-powered applications. The proposed solution is practical, flexible, and cost-effective, providing valuable support for weather-dependent decision-making in remote locations..